Heme Oxygenase-1 Reduces Sepsis-Induced Endoplasmic Reticulum Stress and Acute Lung Injury - Xiaozhen Chen; Yinglin Wang; Xiang Xie; Hongfei Chen; Qiqi Zhu; Zhidong Ge; Hua Wei; Jingshong Deng; Zhengyuan Xia; Qingquan Lian (Mediators of Inflammation)
Background. Sepsis leads to severe acute lung injury/acute respiratory distress syndrome (ALI/ARDS) that is associated with enhanced endoplasmic reticulum (ER) stress. Heme oxygenase-1 (HO-1), an ER-anchored protein, exerts antioxidant and protective functions under ALI. However, the role of HO-1 activation in the development of endoplasmic reticulum (ER) stress during sepsis remains unknown. Methods. Cecal ligation and puncture (CLP) model was created to induce septic ALI. Lung tissue ER stress was measured 18 hours after CLP. The effects of HO-1 on ER stress during septic ALI were investigated in vivo using HO-1 agonist hemin and antagonist ZnPP. Results. Compared with the sham group, ER stress in septic lung increased significantly 18 hours after CLP, which was significantly reduced by pretreatment with the ER inhibitor 4-phenylbutyrate (4-PBA). The lung injury score and the lung wet to dry (W/D) ratio in lungs were significantly reduced in septic rats after ER stress inhibition. Similarly, lung ER stress-related genes’ (PERK, eIF2-α, ATF4, and CHOP) levels were attenuated after ER stress inhibition. Furthermore, HO-1 activation by hemin reduced p-PERK, p-eIF2-α, ATF4, and CHOP protein expression and oxidative stress and lung cell apoptosis. Additionally, HO-1 antagonist could aggregate the ER stress-related ALI. Conclusions. ER stress was activated during CLP-induced ALI, which may represent a mechanism by which CLP induces ALI. HO-1 activation could inhibit CLP-induced lung ER stress and attenuate CLP-induced ALI.